2021
DOI: 10.3390/antibiotics10060652
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol-Based Combination Therapy for “Difficult-to-Treat” Gram-Negative Severe Infections: Real-Life Case Series and Future Perspectives

Abstract: Cefiderocol is a new cephalosporin displaying against extensively resistant (XDR) Gram-negative bacteria. We report our experience with cefiderocol-based combination therapies as “rescue” treatments in immunocompromised or critically ill patients or in patients with post-surgical infections who had failed previous regimens. A total of 13 patients were treated from 1 September 2020 to 31 March 2021. In total, 5/13 (38%) patients were classified as critically ill, due to severe COVID-19 lung failure; 4/13 (31%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 75 publications
4
79
0
Order By: Relevance
“…All these factors could affect the antibiotic pharmacodynamic and pharmacokinetic aspects and may influence clinical outcome. Finally, these favourable outcomes are even more relevant since almost 90% of the patients were admitted to intensive care and they all had an extended follow-up of 90 days, significantly longer than other published case series, 11 , 13 and 30% of our cases were critically ill COVID-19 patients with a VAP due to XDR/DRT-P, associated per se with a significantly increased 28 day mortality rate. 14 …”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…All these factors could affect the antibiotic pharmacodynamic and pharmacokinetic aspects and may influence clinical outcome. Finally, these favourable outcomes are even more relevant since almost 90% of the patients were admitted to intensive care and they all had an extended follow-up of 90 days, significantly longer than other published case series, 11 , 13 and 30% of our cases were critically ill COVID-19 patients with a VAP due to XDR/DRT-P, associated per se with a significantly increased 28 day mortality rate. 14 …”
Section: Discussionmentioning
confidence: 66%
“…Although the rate of clinical cure reported in our study is in line with those previously reported in the larger RCTs, this result is relevant considering the peculiarity of our population. First of all, the prevalence of DRT-P infections was much higher than in previous studies: the rate was only 15% in the CREDIBLE-CR (including also MDR P. aeruginosa ) 5 , 6 and in the study by Bavaro et al ., 11 while no cases were reported by Falcone et al . 12 Only Bleibtreu et al .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in blood isolates, we found consistently high non-susceptibility rates for the aforementioned antibiotics during both pre-pandemic and pandemic periods. P. aeruginosa has been identified as a common coinfecting pathogen in COVID-19 patients causing exacerbation of illness [ 29 , 56 , 60 , 61 , 62 ]. P. aeruginosa has shown high resistance to many antibiotics used during the COVID-period, such as carbapenems [ 48 , 63 , 64 ] and amikacin [ 48 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, CRAB infection-related mortality is highly influenced by the low response to antimicrobials, particularly in the setting of critically ill patients. In fact, the backbone for treatment of CRAB infections is still represented by colistin, an antibiotic burdened by high toxicity and unpredictable pharmacokinetics/pharmacodynamics properties, and clinical data of new therapeutic options, such as cefiderocol, are still urgently needed [61,62].…”
Section: Carbapenem-resistant Non-fermenting Gram-negative Bacteriamentioning
confidence: 99%